Penerapan Ipteks untuk Pengembangan Potensi Limbah Tempurung sebagai Upaya Peningkatan Pendapatan Masyarakat - Muhammad Bukhori Dalimunthe; Rosmala Dewi; Muhammad Andi Abdillah Triono; Dirga Purnama; Hendri Hendri; Fitri Yani Panggabean (Jurnal Pengabdian Pada Masyarakat, 2019)
IMPLEMENTATION OF SCIENCE AND TECHNOLOGY FOR THE DEVELOPMENT OF COCONUT SHELL WASTE AS AN EFFORT TO INCREASE COMMUNITY INCOME. The problems that occur in the community of Sei Paham Village are not yet optimal use of coconut, which is one of the largest coconut production villages in Sei Kepayang District. It requires the acquisition of science and technology in maximizing coconut shell waste into charcoal. The purpose of the service is to implement science and technology in processing coconut shell waste into charcoal as an effort to increase the income of the people of Sei Paham Village. The community empowerment method uses participatory learning and action to be very useful in increasing knowledge and skills by involving community participation in several ways, including: (1) analysis of the situation of potential derivative products from coconut waste; (2) able to design the charcoal combustion devices that have been produced with the service team; and (3) skilled in quality charcoal production. The results of dedication are seen in increasing income and skills in utilizing shell waste. The application of science and technology in developing the potential of shell waste also has a positive impact on the surrounding environment, this is there is no longer a coconut shell buildup because the community has been able to optimize the shell using a coconut shell combustion device to become charcoal.